Disease Characteristics and Treatment Patterns in Veterans With Rheumatoid Arthritis and Concomitant Hepatitis C Infection. Issue 4 (April 2015) - Patel, Ruchika; Mikuls, Ted R.; Richards, John S.; Kerr, Gail; Cannon, Grant W.; Baker, Joshua F.
Abstract : Objective: To assess disease characteristics, disease activity, and treatment patterns in rheumatoid arthritis (RA) patients with comorbid hepatitis C virus (HCV) infection. Methods: RA patients with concomitant HCV were identified within the Veterans Affairs Rheumatoid Arthritis Registry. HCV was defined as at least 1 diagnostic code present in medical record databases. Generalized estimating equations in linear regression models compared component and composite measures of disease activity between HCV‐positive and HCV‐negative patients over the study period, accounting for within‐subject correlations. Similar analysis of pharmacy databases evaluated medication use within each group. Results: Ninety‐two of 1, 706 registry participants (5.1%) were identified with concomitant HCV. At enrollment, HCV‐positive patients were younger (mean ± SD 61.7 ± 7.1 years versus 67.5 ± 11.2 years; P < 0.001), more often African American (35% versus 15%; P < 0.001), and smokers (48% versus 26%; P < 0.001). In unadjusted and adjusted analyses incorporating all study visits, patient‐reported outcomes (pain, tender joints, and patient global scores) were higher in HCV‐positive patients, contributing to higher disease activity scores. There was no difference in physician‐reported outcomes (swollen joints or physician global scores). HCV‐positive patients had lower C‐reactive protein levels (β −0.30 [95% confidence interval (95% CI) −0.53, −0.07], P = 0.01). Over all visits, HCV‐positive patients were less likely to receive methotrexate (odds ratio [OR] 0.27 [95% CI 0.17, 0.40], P < 0.001), and more likely to receive prednisone (OR 1.41 [95% CI 1.02, 1.97], P = 0.04) and anti–tumor necrosis factor α (anti‐TNFα) therapies (OR 1.51 [95% CI 1.04, 2.19], P = 0.03). Conclusion: RA patients with concomitant HCV have higher disease activity scores, driven primarily by higher patient‐reported measures. HCV‐positive patients were more likely to be treated with prednisone and anti‐TNFα therapies and less likely to receive methotrexate compared to HCV‐negative patients.